Temporal Trends and Predictors of Pelvic Lymph Node Dissection in Open or Minimally Invasive Radical Prostatectomy - Feifer, Andrew H. (2011)
BACKGROUND: Pelvic lymph node dissection (PLND) is an important component of prostate cancer staging and treatment, especially for surgical patients with high-risk tumor features. It is not clear how the shift from open radical prostatectomy (ORP) to minimally invasive radical prostatectomy (MIRP) has affected use of PLND. Our objective was to identify predictors of PLND and assess the impact of surgical technique in a contemporary, population-based cohort. METHODS: In Surveillance, Epidemiology, and End Results (SEER) cancer registry data linked with Medicare claims, we identified men who had ORP or MIRP for prostate cancer in 2003–2007. We evaluated the impact of surgical approach on PLND and examined interactions between surgical procedure, PSA and Gleason score, controlling for patient and tumor characteristics. RESULTS: Of 6,608 men who had ORP or MIRP, 70% (n=4,600) had PLND. Use of PLND declined over time, overall and within subgroups defined by procedure type. PLND was 5 times more likely in men receiving ORP than MIRP, controlling for patient and tumor characteristics. Elevated PSA and biopsy Gleason score, but not clinical stage, were associated with greater odds of PLND in both ORP and MIRP groups. However, the magnitude of the association between these factors and PLND was significantly greater for ORP patients. CONCLUSION: PLND was less common in men who received MIRP, independent of tumor risk factors. A decline in PLND rates was not fully explained by an increase in MIRP. These trends may signal a surgical approach-dependent disparity in prostate cancer staging and therapy.